A Relational-Cultural Approach to Examining Concealment among Latter-Day Saint Sexual Minorities - Skidmore, Samuel J. (Religions, 2024)
Sexual minorities often conceal their sexual identity from others to avoid distal stressors. Such concealment efforts occur more frequently among sexual minorities in religious settings where rejection and discrimination are more likely. Using a sample of 392 Latter-day Saint (“Mormon”) sexual minorities, we assess (a) the effect of religious affiliation on concealment efforts, (b) the relationship between social support, authenticity, and religious commitment on concealment, and (c) the moderating effect of authenticity on religious commitment and concealment. Multi-level model analyses revealed that religious affiliation alone accounted for over half (51.7%) of the variation in concealment efforts for Latter-day Saint sexual minorities. Social support directly was related to less concealment, whereas religious commitment was related to more concealment, with authenticity moderating the impact of religious commitment on concealment efforts. The present study provides insight into how religious sexual minorities may approach relationships and inadvertently wound their chances to connect with others.